From Palestine to Israel : a photographic record of destruction and state formation, 1947-1950 - Azoulay, Ariella (Pluto, 2011)
"In this carefully curated and beautifully presented photobook, Ariella Azoulay offers a new perspective on four crucial years in the history of Palestine/Israel. The book reconstructs the processes by which the Palestinian majority in Mandatory Palestine became a minority in Israel, while the Jewish minority established a new political entity in which it became a majority ruling a minority Palestinian population. By reading over 200 photographs from that period, most of which were previously confined to Israeli state archives, Azoulay recounts the events and the stories that for years have been ignored or only partially acknowledged in Israel and the West."--Publisher website